PEMEKARAN DAERAH: PELUANG DAN TANTANGAN BAGI PEMEKARAN KOTA MEULABOH - Ikhsan Ikhsan (Universitas Teuku Umar, 2016)
The Establishment of the new city has two consequences. Positive consequence of the creation of new district is the best solution for the old and new in infrastructure development. The negative consequence occure when the creation of new district is only focus on development of new infrastructure for the central office administration and ignore the poverty and welfare as the main problem of societyKeywords: Decentralization, Expansion, Poverty